A Comparative study of Extra-Amniotic Instillation of Ethacridine with Tablet Dinoprostone (PGE2) in Second Trimester Abortion Versus Ethacridine Alone - Kour, Sandeep; Kour, G (Nepal Journal of Obstetrics and Gynaecology, 2013)
Aims: To study the efficacy of combination of extra-amniotic instillation of ethacridine with tablets Dinoprostone (PGE2) in second trimester abortion as compared to ethacridine alone. Methods: One hundred patients undergoing second trimester abortion were divided into two groups. Fifty patients received extra-amniotic ethacridine lactate 150 ml through Foley’s catheter (Ethacridine group) and the other 50 patients received 150 ml extra-amniotic ethacridine lactate mixed with a 0.5 mg of a crushed tablet of Dinoprostone through Foley’s catheter (Combination group). Both the groups were compared in respect to instillation-abortion interval, completeness of abortion and success rate. Results: The mean age, multiparity parity, and gestational age were comparable in both the groups. The instillation- abortion interval was significantly shorter in combination group as compared to ethacridine group (16.4±7.1 vs. 29.9 ±13.9 hours, p<0.001). Two patients in combination group had instillation abortion interval more than 48 hours as compared to 16 patients in ethacridine group(p<0.0005). Forty one patients (82%) in combination group had complete abortion as compared to 37 (74%) patients in ethacridine group. The success rate was 48/50(96%) in combination group as compared to 45/50 (90%) in ethacridine group. Conclusions: Addition of a 0.5 mg of crushed tablet of Dinoprostone in extra-amniotically instilled ethacridine lactate reduced the instillation-abortion interval significantly, increased the chances of complete abortion and increased the success rate. Nepal Journal of Obstetrics and Gynaecology / Vol 7 / No. 1 / Issue 13 / Jan- June, 2012 / 25-27 DOI: http://dx.doi.org/10.3126/njog.v7i1.8831